Conventional Implicature in Persuasive Speech Acts of the Song Syi'ir Tanpa Waton and Its Pedagogical Relevance to Javanese Literary Text in Senior High Schools - Ahmad Rizky Wahyudi; Ina Ika Pratita; Riki Nasrullah (Journal of Pragmatics Research, 2025)
Conventional implicature in persuasive speech acts serves as an effective linguistic mechanism for delivering moral messages and noble values in a refined manner, as exemplified in the Javanese religious song Syi'ir Tanpa Waton. This study aims to examine nine selected data units from a total of thirteen stanzas in the song’s lyrics, which serve as the primary data. A descriptive qualitative approach was employed, with data collected through documentation and textual analysis of the lyrics. The analysis draws on Grice’s theory of implicature and Searle’s speech act theory, focusing on the illocutionary dimension of the speech acts. The findings indicate that the persuasive speech acts identified in the lyrics consist of prohibitions, indirect criticisms, exhortations, and declarative expressions, all of which are imbued with deep spiritual meaning. These speech acts reflect conventional implicature through specific lexical and grammatical markers in Javanese, which encode implied messages independent of conversational context. The study demonstrates significant relevance to Javanese language learning at the senior high school level, particularly in the area of literary text instruction, where students are encouraged to interpret implicit meaning and internalize local wisdom. Implementation in classroom settings may enhance students' interpretative skills while simultaneously reinforcing cultural identity. In addition to enriching pragmatic-semantic analysis of contemporary Javanese texts, this research offers a pedagogical model that integrates culturally rooted literary works into meaningful and engaging language instruction for younger generations.